Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2026)
This issue of the Law, State and Telecommunications Review is a special issue that brings together selected articles from the most recent International Conference CPRLATAM2025, held in Buenos Aires. This issue includes articles on the AI gap between Latin American countries, energy sustainability in the face of increasing demand for data centers in Latin America, the application of AI to address the digital divide through mapping of unconnected areas, the environmental impact of public digital infrastructures in Peru, and the digital ecosystem of security and trust in Latin America.